The 30-day readmission rate of same-day discharge protocol following catheter ablation for atrial fibrillation: a propensity score-matched analysis from National Readmission Database. Issue 5 (14th December 2021) - Sahashi, Yuki; Kuno, Toshiki; Tanaka, Yoshihiro; Passman, Rod; Briasoulis, Alexandros; Malik, Aaqib H
Abstract: Aims: The effectiveness and safety of same-day discharge (SDD) for catheter ablation (CA) for atrial fibrillation (AF) has not been fully elucidated using a large nationwide database. This study aimed to evaluate the all-cause readmission rates within 30-days among patients receiving CA for AF with an SDD protocol compared with a conventional overnight stay (ONS). Methods and results: We performed a retrospective cohort study using the US Nationwide Readmission Database. The primary outcome was all-cause 30-day readmission following discharge in patients receiving CA and a secondary outcome was requiring total healthcare cost. A 1 : 3 propensity score matching was conducted to compare the safety and efficacy within both SDD and ONS group. Among 30 776 patients [mean 67.2 ± 11.4 years, 12 590 female (41.5%)] who received CA from 2016 through 2018, 440 (1.42%) patients were discharged on the same-day following CA (SDD group), and the remaining 30 336 patients stayed at least one night in the hospital (ONS group). A propensity score analysis generated 1751 matched pairs (440 in the SDD group; 1311 in the ONS group). The 30-day readmission following discharge was not significantly higher in the SDD group than the ONS group (SDD vs. ONS: 12.7% vs. 9.7%; hazard ratio: 1.17, 95% confidence interval: 0.76–1.81, P = 0.47). Healthcare cost was significantly higher in the ONS group (25 237 ± 14 036 vs. 30 749 ± 16 383; P < 0.01). Conclusion: In this nationwide database study, there was no significant difference in the all-cause 30-day readmission following SDD for CA compared with ONS. Graphical Abstract: